PEMBELAJARAN IPS BERBASIS RESEARCH - Tusriyanto Tusriyanto (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Social studies learning should be emphasized on skills to participate in the society. Social studies has the value of practical learning, which should foster creative individuals, democratic and full responsibility, and simultaneously has the burden of cultural development as well as a good life, harmonious and dynamic. Social studies research-based learning activities, sticking to the line of thought of research, which started its activities by seeking a variety of problems, formulate problems, data collection, data analysis and draw conclusions is the answer to the problem formulation. Social studies research-based learning is expected to equip the ability of social knowledge, the ability to identify, analyze, organize alternative social problem-solving, the ability to communicate with other community members as well as various other accompaniment capabilities.